TES KESEHATAN PRA NIKAH BAGI CALON MEMPELAI LAKI- LAKI DI KANTOR URUSAN AGAMA (KUA) JATIREJO MOJOKERTO - Hana Ayu Aprilia (State Islamic University (UIN) of Sunan Ampel, 2017)
This article examines the implementation of â€œpre-marriage health test for bride and groom in Religious Affairs Office (KUA) of Jatirejo Sub-district, Mojokerto Regency on the maslahah mursalah perspectiveâ€. Pre-marriage health test in Religious Affairs Office (KUA) of Jatirejo Sub-district, Mojokerto Regency is solely done for bride and groom. The Public Health Center (Puskesmas) asks globally about history of disease, height, and weight of the bride and groom. In Islam, it is permissible (mubah) and included in hajiyyah benefit. The pre-marriage health test is one of the efforts to keep the offspring (hifz al-Nasl). Pre-marriage health test that should be done by both bride and groom gives many benefits. One of them is to prevent the transmission of disease like mentioned in the phrase â€œprevention is better than cureâ€, the government should also provide convenience to community by reducing the cost of medical examination.